2017
DOI: 10.1002/lno.10760
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging processes on jellyfish carcasses across a fjord depth gradient

Abstract: Gelatinous zooplankton populations have increased in some regions, specifically Norwegian fjords, which has likely increased the occurrence of dead jellyfish aggregations on the seafloor (jelly‐falls). The importance of scavengers in the redistribution of organic material from jelly‐falls and their biogeochemical influence on the benthic environment has been demonstrated. However, scavenger responses to jelly‐falls across environmental gradients have not been studied, but would significantly advance our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…If not consumed, intact jellyfish corps continue sinking through the water column as jelly-falls (term coined by Billett et al 2006;Lebrato and Jones 2009;Lebrato et al 2011;Sweetman and Chapman 2011) and the OM contained within their biomass could be transferred in a cascade to different members of the marine food web. Potential scavengers, such as macrofauna and megafauna, might fragment jellyfish bodies, as experimentally shown (Sweetman et al 2014), with no significant depth effect on mean scavenging rates (Dunlop et al 2018). In addition, fragmentation of jelly carcasses during sinking could also occur under turbulent conditions in the upper mixed water column, as previously reported for different size-ranges of particles in the ocean (Briggs et al 2020 and the references therein).…”
Section: The Fate Of Jellyfish Detritusmentioning
confidence: 95%
See 1 more Smart Citation
“…If not consumed, intact jellyfish corps continue sinking through the water column as jelly-falls (term coined by Billett et al 2006;Lebrato and Jones 2009;Lebrato et al 2011;Sweetman and Chapman 2011) and the OM contained within their biomass could be transferred in a cascade to different members of the marine food web. Potential scavengers, such as macrofauna and megafauna, might fragment jellyfish bodies, as experimentally shown (Sweetman et al 2014), with no significant depth effect on mean scavenging rates (Dunlop et al 2018). In addition, fragmentation of jelly carcasses during sinking could also occur under turbulent conditions in the upper mixed water column, as previously reported for different size-ranges of particles in the ocean (Briggs et al 2020 and the references therein).…”
Section: The Fate Of Jellyfish Detritusmentioning
confidence: 95%
“…Importantly, most of these are records of cnidarian carcasses, while as emphasized by Luo et al (2020), there are no records of benthic depositions of ctenophores. If deposited at the seafloor, jellyfish carcasses would be either scavenged (Sweetman et al 2014; Dunlop et al 2017, 2018) or degraded and remineralized by the benthic community ( Lebrato and Jones 2009; West et al 2009; Chelsky et al 2016; Sweetman et al 2016; Dunlop et al 2017). It has been shown that the degradation rate by the benthic community may change as a function of water column O 2 availability (Billett et al 2006; Sweetman and Chapman 2011, 2015).…”
Section: Links Between Jellyfish and Microbesmentioning
confidence: 99%
“…In all cases, however, jelly-C depositions impact the dynamics of seawater carbon and nutrient cycling, as well as overall water and localized benthic chemistry and microbial respiration (West et al, 2009;Sweetman et al, 2016). To date, assessments of the responses of macro-and megafaunal communities along bathymetric gradients in continental margins that are naturally enriched with jelly-C are unknown, except from experiments that used manually placed bait (Sweetman et al, 2014;Dunlop et al, 2017;Dunlop et al, 2018) and examinations of fixed stations only at single depths (Smith et al, 2014). Thus, in this study, we sought to combine observations from a benthic remotely operated vehicle (ROV) video survey and from water column profiles off the Ivory Coast of West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In benthic deep-sea systems, inorganic carbon fixed via prokaryotes (so-called "dark fixation") may also provide significant carbon sources (Molari et al, 2013;Sweetman et al, 2019). Occasionally, large pulses of food arrive at the bottom of the ocean in the form of carcasses of large animals such as whale/shark falls, or mass mortality of jellyfish (e.g., Higgs et al, 2014;Dunlop et al, 2018) or even from terrestrial sources by wood-falls or large inputs of sediment (e.g., Dando et al, 1992;Holding et al, 2017;Sen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%